Optimalisasi Preventive Maintenance Ground Power Unit pada Perawatan Pesawat Udara di PT. IAA AMO Menggunakan Metode FMEA - Kurniawan, Sandi; Apriliana Sari Wulandari, Indah; Sukmono, Tedjo (Industrial Engineering, Engineering of Faculty, Universitas Kadiri, 2024)
High operational costs and downtime risks can affect industry efficiency making equipment maintenance optimization an urgent need. PT. IAA AMO, as a manufacturing industry in the field of aircraft maintenance, faces significant challenges with the low reliability of Ground Power Unit (GPU) engines which only reaches 86%. This has led to an increase in the company's operating costs. The purpose of this study is to optimize Preventive maintenance on the Ground Power Unit (GPU) in aircraft maintenance at PT. IAA AMO using the Failure Mode and Effect Analysis (FMEA) method. The results show that the MTTF of the GPU is 311 hours, while the MTBF is 373 hours. To prevent sudden breakdowns, preventive maintenance is recommended every 311 hours for non-repairable components and 373 hours for repairable components. This research offers a more effective maintenance strategy to improve GPU reliability and lower operational costs. This research results in more effective maintenance planning, which not only minimizes downtime and operational costs, but also improves the overall reliability of the GPU machine. With the implementation of FMEA methods and the right preventive maintenance strategy, companies can anticipate breakdowns early, extend engine life, and ensure smooth operations in support of aircraft maintenance.